2018
DOI: 10.5232/ricyde2018.05406
|View full text |Cite
|
Sign up to set email alerts
|

Asimetrías neuromusculares entre miembros inferiores en jugadores de hockey sobre patines. [Lower limb neuromuscular asymmetry in roller hockey players].

Abstract: El objetivo de este trabajo fue comparar y cuantificar las asimetrías neuromusculares entre las extremidades inferiores que presentan los jugadores de hockey sobre patines. Un objetivo secundario fue correlacionar el índice de asimetrías (ASI) entre las diferentes pruebas neuromusculares testadas. Un total de 27 jugadores de sexo masculino de hockey sobre patines (edad = 20,59 ± 3,81 años) realizaron diferentes pruebas neuromusculares de forma unilateral: 1) Test de salto vertical con contra-movimiento (SLCJ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
3
3
2
Order By: Relevance
“…The kappa coefficient, calculated to know the direction of asymmetries, showed only "fair" side consistency of asymmetry between tests (−0.36 to 0.23). These results are in accordance with Arboix-Alió et al [16] who found no significant relationships between the asymmetry values of different neuromuscular tests in rink hockey players. In line with other studies in different team sports, the present investigation failed to demonstrate the relationship between asymmetry scores on different tests [13,46,47].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The kappa coefficient, calculated to know the direction of asymmetries, showed only "fair" side consistency of asymmetry between tests (−0.36 to 0.23). These results are in accordance with Arboix-Alió et al [16] who found no significant relationships between the asymmetry values of different neuromuscular tests in rink hockey players. In line with other studies in different team sports, the present investigation failed to demonstrate the relationship between asymmetry scores on different tests [13,46,47].…”
Section: Discussionsupporting
confidence: 92%
“…The highest mean was obtained in the SLCJ-V test (8.09 ± 6.86 %). This value is slightly lower than the mean reported by Arboix-Alió et al [16] (9.60%) in a similar sample. Similarly, the ASI mean values for the SLCJ-H (2.91 ± 2.62%) and COD (2.16 ± 1.55%) tests were also lower than those reported by Arboix-Alió et al [16].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Asymmetries observed in the different functional tests also showed notable differences. This finding is in line with Fort-Vanmeerhaeghe et al (2015) and Arboix-Alió et al (2018) who did not find a relationship between the ASI values of different neuromuscular tests in basketball and roller hockey players, respectively. Moreover, in several players, the HPL differed between tests, showing the task-specific nature of both the direction of asymmetry and superior performance capabilities.…”
Section: Discussionsupporting
confidence: 88%
“…The authors point out the lack of clear criteria for asymmetry. Arboix-Alio et al [22] evaluated the effectiveness of various neuromuscular tests for assessing asymmetry in roller hockey. A large number of tests increases the significance of the results.…”
Section: Discussionmentioning
confidence: 99%